An Overview of Waste Milk Feeding Effect on Growth Performance, Metabolism, Antioxidant Status and Immunity of Dairy Calves - Ma, Yulin; Khan, Muhammad Zahoor; Xiao, Jianxin; Alugongo, Gibson Maswayi; Chen, Xu; Li, Shengli; Wang, Yajing; Cao, Zhijun (Frontiers in Veterinary Science, 2022)
Waste milk (WM) is a part of milk produced on dairy farms that is not suitable for human consumption. Waste milk contains transition milk, mastitis milk, colostrum, milk somatic cells, harmful pathogens and antibiotic residues. Due to the high cost of milk replacer, dairy farmers prefer to utilize waste milk as a feed to their calves. It has been well established that WM has a high nutritive value comparatively which can contribute to improved growth, rumen development, and immune-associated parameters when fed to dairy calves. However, feeding WM to calves before weaning has continuously raised some critical concerns. The pathogenic load and antibiotic residues in waste milk may increase the risk of diseases and calves' antibacterial resistance. Thus, pasteurization has been recommended as an effective method because this technique may help to decrease diseases risk in calves by killing/inhibiting the pathogenic microorganisms in WM. Altogether, the current review has provided a brief overview on the interplay between the positive role of WM on overall calf performance, the limitations of WM as a feed source and how to overcome on these issues raised due to WM feeding.